Faculty Mindsets in the Era of COVID-19 (International Journal of Multidisciplinary Perspectives in Higher Education, 2020)
With the disruption caused by COVID-19, the higher education community has begun to share resources and ideas for successfully transitioning to the “new normal” of teaching. While many conversations focus on concrete strategies for adapting teaching, I focus here on ways to address the psychological burden these changes have brought. Specifically, I provide suggestions for shifting our teaching mindsets to be growth oriented so that we can successfully provide instruction to students despite the challenges imposed by COVID-19.